2010
DOI: 10.1007/s11205-010-9591-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Individual Secularism Promote Life Satisfaction? The Moderating Role of Societal Development

Abstract: Life satisfaction, Secular values, Subjective well-being, Human development index,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…more traditionally oriented countries -showing a strong conformity mechanism in explaining the relationship between marriage and life-satisfaction. This finding fits in with similar research on conformity effects for value orientations (Li & Bond 2010) and religiosity (Eichhorn 2011). Finally, we also find that the positive marriage effect was more prevalent in older-age societies -which of course makes sense considering the importance of traditional orientations.…”
Section: Contextualising the Effects Of Being Married On Life-satisfasupporting
confidence: 91%
See 2 more Smart Citations
“…more traditionally oriented countries -showing a strong conformity mechanism in explaining the relationship between marriage and life-satisfaction. This finding fits in with similar research on conformity effects for value orientations (Li & Bond 2010) and religiosity (Eichhorn 2011). Finally, we also find that the positive marriage effect was more prevalent in older-age societies -which of course makes sense considering the importance of traditional orientations.…”
Section: Contextualising the Effects Of Being Married On Life-satisfasupporting
confidence: 91%
“…Pointing in a similar direction are investigations distinguishing between different forms of value orientations and their impact on life-satisfaction. Li & Bond (2010) show that effects of personal attitudes can only be evaluated with regards to their effect on subjective well-being when taking into account prevailing value structures in the respective societies highlighting the importance of a certain amount of congruence between individuals and the respective societies they live in. Delhey 2010demonstrates that in economically richer societies post-materialistic value orientations enhance life-satisfaction, while the importance of material characteristics decreases.…”
Section: Cultural Context Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This context-dependency has 18 PURPOSE-DRIVEN LIFE been reported by, for example, La Barbera and Gürhan (1997), who found that the negative correlation of materialism and well-being only existed in born-again Christians and not in nonborn-again Christians. Another finding supporting the context-dependent view was reported by Li and Bond (2010). They noted a positive correlation between secularist values and life satisfaction in highly-developed nations.…”
Section: Discussionsupporting
confidence: 69%
“…Pointing into a similar direction are investigations distinguishing between different forms of value orientations and their impact on life-satisfaction. Li & Bond (2010) show that effects of personal attitudes can only be evaluated with regards to their effect on subjective well-being when taking into account prevailing value structures in the respective societies highlighting the importance of a certain amount of congruence between individuals and the respective societies they live in -a finding further substantiated by Eichhorn (2011) regarding the effect of religiosity on lifesatisfaction. Delhey (2010) demonstrates that in economically richer societies postmaterialistic value orientations enhance life-satisfaction, while the importance of material characteristics decreases.…”
Section: Attitudinal or Cultural Factorsmentioning
confidence: 92%